Finite element simulation of rectangular concrete-filled steel-hollow section beam-column structure - Shahrbijari, Kamyar Bagherinejad (2013)
Composite steel–concrete construction is widely used in the construction of modern buildings and bridges, even in regions of high seismic risk. Despite the excellent engineering properties of concrete filled tubs (CFT), they are not as widely used as traditional structural steel and reinforced concrete members. Although much research has been performed on the topic, the amount of information regarding CFTs is significantly less than that available for traditional steel or reinforced concrete members. The aim of this study is to predict the buckling behavior of concrete-filled steel hollow structural section beamcolumns with advanced finite element methods, then compare the predictions with experimental results found from literature. It is also optimize findings and represent a finite element model for further studies. In this study the modeling and non-linear analysis of beam-column specimens is perform using ABAQUS finite element software. A total of two different specimens from experimental study were investigated with eccentric loading. The specimens have square section with overall depth of 120 mm and 140 mm respectively. Two different models were established, to investigate bending behavior of rectangular sections with overall depth of 120 mm and 140 mm. The steel tube section thickness for all sections was 3.84 mm. The tests were performed on pin-ended Beamcolumns. It is found that the buckling shape and the displacements predicted from ABAQUS are in good agreement to those observed experimentally. ABAQUS non-linear Finite element analysis can be also used to predict the ultimate load of concrete filled steel tube members